Cognitive Behaviour Therapy to Overcome Trauma of A Child Sexual Abuse Victim in Bandung-Indonesia - Ellya Susilowati; Krisna Dewi (Asian Social Work Journal, 2019)
Cognitive Behavior Therapy (CBT) is a micro social work intervention technique that can reduce trauma experience by victims of sexual violence, including children. The purpose of this study was to examine and analyze the application of CBT interventions in dealing with the trauma as experienced by a 10-year-old girl, a victim of sexual violence, who gets help from the Child Protection Agency (LPA) in Bandung. This study used experimental approach with Single Subject Design (SSD) with A-B measurement technique to show the impact of the interventions result. Trauma indications that are intervened with the CBT model are the fear of being alone, nightmare, and sadness when hearing the words related to rape or sexual violence. CBT interventions carried out in this study are performed by providing psychoeducation, relaxation, helping the victim to express feelings, teaching coping skills, and in vivo exposure. The results of CBT interventions indicated changes in the reduction in frequency of trauma indications in children who are victims of sexual violence. This proves that CBT interventions can be performed to reduce the trauma experienced by the 10-year-old victim of sexual violence. The recommendation that can be suggested based on the results of this study are; CBT should be carried out with a more complete session and give reinforcement to parents about mentoring traumatic child victims of sexual violence